Enhancing Built‐in Electric Fields for Efficient Photocatalytic Hydrogen Evolution by Encapsulating C60 Fullerene into Zirconium‐Based Metal‐Organic Frameworks. (6th February 2023) - Liu, Liping; Meng, Haibing; Chai, Yongqiang; Chen, Xianjie; Xu, Jingyi; Liu, Xiaolong; Liu, Weixu; Guldi, Dirk M.; Zhu, Yongfa
Abstract: High‐efficiency photocatalysts based on metal‐organic frameworks (MOFs) are often limited by poor charge separation and slow charge‐transfer kinetics. Herein, a novel MOF photocatalyst is successfully constructed by encapsulating C60 into a nano‐sized zirconium‐based MOF, NU‐901. By virtue of host‐guest interactions and uneven charge distribution, a substantial electrostatic potential difference is set‐up in C60 @NU‐901. The direct consequence is a robust built‐in electric field, which tends to be 10.7 times higher in C60 @NU‐901 than that found in NU‐901. In the catalyst, photogenerated charge carriers are efficiently separated and transported to the surface. For example, photocatalytic hydrogen evolution reaches 22.3 mmol g −1  h −1 for C60 @NU‐901, which is among the highest values for MOFs. Our concept of enhancing charge separation by harnessing host‐guest interactions constitutes a promising strategy to design photocatalysts for efficient solar‐to‐chemical energy conversion. Abstract : Isolated C60 molecules are encapsulated in a Zr‐based NU‐901 metal‐organic framework (MOF) to obtain a C60 @NU‐901 composite. Host‐guest interactions amplify the irregular charge distribution of the system, giving rise to an enhanced built‐in electric field that promotes efficient charge separation and transportation of carriers. The composite mediates photocatalytic H2 production under visible light.